Oral hygiene practice and periodontal status among two tribal population of Telangana state, India- an epidemiological study - Shaik Mohammed Asif; Shaik Naheeda; Khalil Ibrahim Assiri; Hussain Mohammed Almubarak; Sultan Mohammed Kaleem; M. Zakirulla; Fawaz Abdul Hamid Baig; Mohammed Zahir Kota (BMC, 2019)
Abstract Background The tribes of India have poor periodontal health status due to their isolation, awareness and less accessibility to dental resources. They follow traditional methods of oral hygiene practice, which are found to be inadequate and inaccurate to maintain their good oral health. This study aims to assess the oral hygiene practice, oral hygiene and periodontal status of two tribes residing in Bhadrachalam, Telangana, India. Methods Based on accessibility the two tribes Koya and Lambada were included in the study. The total study population consisted of 1000 subjects, with 500 subjects in each group. Using a preformed proforma the oral hygiene practices were recorded for two groups and oral examination was done using Oral Hygiene Index (OHI-S) index and Community Periodontal Index (CPI). Results The OHI-S ranged between 2.5-3.0 in both the groups. The CPI index scores showed that sextants with calculus, shallow pockets, deep pockets and loss of attachment of 4-5 mm were significantly present in both groups. Conclusion To conclude, though practice of poor oral hygiene and compromised periodontal status was seen among both groups. However, it was more prevalent in Koya. Under these circumstances, implementation of a basic awareness of oral health care programme for these tribes should be a high priority.